Accessibility and comprehension of COVID-19 information for people with blindness and low vision - Mašić Fabac, Valentina; Sikirić, Dominik (Specijalna edukacija i rehabilitacija, 2023)
Introduction. In crisis situations like the COVID-19 pandemic, timely and comprehensive health information for people with blindness and low vision is extremely important. Based on the information gathered, it is possible to respond appropriately to the health services needs of the pandemic. Objectives. The purpose of this study was to define the differences in demographic groups among 45 adults with visual impairment from Croatia in accessibility and comprehension of COVID-19 information during the lockdown and its impact on emotional distress and adherence to epidemiological measures. Methods. Mann-Whitney and Kruskal-Wallis tests were used to test for differences between demographic groups on the information accessibility and comprehension variables. Spearman’s test of correlation coefficient was used to test the correlation between information accessibility and comprehension with emotional distress and adherence to epidemiologic measures. Results. The results showed a statistically significant difference for people with blindness and low vision older than 60 who have fewer problems than those 20-30 years old in the COVID-19 information accessibility. Those with higher information accessibility left their houses more rarely. Information accessibility showed no correlation with emotional distress. People with blindness and low vision with higher information comprehension expressed lower emotional distress and felt more certain about proper house hygiene upkeeping. Conclusion. Higher attention should be given to the accessibility and comprehension of media information for people with blindness and low vision in critical situations that can lead to saving lives, in the case of the COVID-19 pandemic, by lessening social contact and keeping proper house hygiene.